Фреймова структура концепту Тероризм - Семенчук, Алла Борисівна; Semenchuk, A. B. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Стаття присвячена дослідженню особливостей фреймової структури концепту ТЕРОРИЗМ. Аналіз способів та засобів об’єктивації зазначеного концепту показує сприйняття об’єктивної дійсності крізь призму певної ідеології та менталітету. При цьому відбувається концептуалізація учасників конфлікту в термінах базових цінностей ДОБРА і ЗЛА, підґрунтям якої слугує дихотомія свій : : чужий. Проекцією цієї опозиції у концепті ТЕРОРИЗМ виступає протиставлення Захід : : Схід. The article focuses on linguistic and cognitive peculiarities of the concept TERRORISM and specifies its actualizing in the English language with the help of innovations. The frame-based approach is the best way to describe the concept’s structure, made up of slots with their specifications and represent relations between its constituents. The author also highlights the phenomenon of the war of linguistic signs which includes the war of form (when warring parties use different lexical means to define each other) and the war of meaning (when warring parties use the same lexical units but with altered meaning to call each other). The means of verbalization of the concept TERRORISM reflect the perception of reality in the light of a certain ideology and mentality. The conceptualization of conflicting parties is here based on the dichotomy Occident : : Orient, reflecting the opposition between western and eastern civilizations.
Frame Structure of the Concept Terrorism
Keywords: фреймова структура; frame structure; концепт ТЕРОРИЗМ; concept TERRORISM; слот; slot